Living tools: an environmental history of afforestation and the shifting image of trees - Young, Theresa L. (Kansas State University, 2013)
In the second half of the nineteenth century, the Timber Culture Act (1873) and the development of the field of scientific forestry shifted the social conception of trees from a cultural icon, into living technological tools. Beginning with the antebellum publications of George Perkins Marsh, who argued for the preservation and restoration of forests for the benefit of all, scientists, railroad developers, and plains settlers advocated for the cultural importance of trees as a living tool. Assured by railroad-boosters, the budding Forestry Bureau, and pro-tree legislators that rainfall would follow their planting efforts, waves of emigrants who relocated to the grasslands from the eastern forested areas planted millions of trees in an attempt to afforest the open prairies, creating traceable environmental and social changes over time. Environmental historian Elliott West asserts, “Only people have tried on a massive scale to move imagined environments out of their heads and to duplicate them in the world where others live,” and the grasslands of Kansas is one of these environments. This thesis argues that the scientific field of forestry developed a system of prairie tree planting (afforestation) aimed at altering the environment of the Great Plains with artificial forests and created a technological construction of the Kansas environment. The enactment of the Timber Culture Act was a watershed moment because it elevated the social conceptions of trees to that of a living tool and created the need for a national Forestry Bureau. Primary source documents reveal that the general perception held in the nineteenth century was that the natural environment and climate was malleable. The development of profit-centered tree farms furthered the idea that forests were like any other manageable crop. The changes over time in the forest cover of Kansas resulted in an altered ecology and the introduction of invasive species, but most importantly, it altered the cultural perception of how Kansas should look.
Keywords: Environmental History; Kansas History; History of Technology; Timber Culture Act; Afforestation; History; Environmental Studies (0477); Forestry (0478); History (0578)